Perbedaan Kualitas Hidup Lansia yang Tinggal di Komunitas dengan di Pelayanan Sosial Lanjut Usia (The Different of Quality of Life Among the Elderly who Living at Community and Social Services) - Amalia Yuliati; Ni'mal Baroya; Mury Ririanty (Pustaka Kesehatan, 2014)
Quality of life is a very board concept that was affected by individual physical condition, psychological, level of independence, and individual's relationship with the environment. This research aimed to determine differences in the quality of life of the elderly who living at community and Social Services, according to the physical, psychological, social, and environmental domain. This research was analytically studies using cross sectional design. The number of sample was 210 respondent. Mann Whitney and Kruskal Wallis test (alpha 0,05) was applied to analyze the data. There were not significant difference between quality of life of the elderly living at community and at Social Services in Jember (p=1.000). Based on domain quality of life, the were significant difference between physical, psychological, social, and environmental domain of the elderly living at community and Social Services in Jember.   Keywords: elderly people, quality of life, community, Social Services